Molecular phylogeny and bioprospecting of Endolichenic Fungi (ELF) inhabiting in the lichens collected from a mangrove ecosystem in Sri Lanka - Maduranga, Kasun (PLoS One, 2018)
Endolichenic fungi (ELF) are unexplored group of organisms as a source for the production of bioactive secondary metabolites with radical scavenging activity, antilipase and amylase inhibitory activities. Endolichenic fungi in lichens collected from mangrove or mangrove associated plants are least known for their fungal diversity and potential to produce bioactive compounds. A total of 171 ELF strains were isolated from the lichens collected from mangrove and mangrove associated plants in Puttalam lagoon. Out of this collection, 70 isolates were identified using rDNA-ITS region sequence homology to the GenBank accessions and a phylogenetic analysis was performed. Commonly isolated genera of ELF from lichens were Aspergillus, Byssochlamys, Talaromyces, Diaporthe, Phomopsis, Endomelanconiopsis, Schizophyllum, Cerrena, Trichoderma, Xylaria, Hypoxylon, Daldinia, Preussia, Sordaria, Neurospora, and Lasiodiplodia. In the present study, the effectiveness of ethyl acetate extracts of the ELF isolates were investigated against antioxidant activity, antilipase activity and α-amylase inhibition activity in in-vitro conditions. The results revealed that the extracts of Daldinia eschscholtzii, Diaporthe musigena and Sordaria sp. had the highest radical scavenging activity with smaller IC(50) values (25 μg/mL to 31 μg/mL) compared to the IC(50) values of BHT (76.50±1.47 μg/mL). Antilipase assay revealed that 13 extracts from ELF showed promising antiobesity activity ranged between 25% to 40%. Amylase inhibitory assay indicated that the test extracts do not contain antidiabetic secondary metabolites.